Seismic Expression of Key Geological Features in the East Natuna Basin - Herman Darman (Berita Sedimentologi, 2017)
The East Natuna Basin is located in the southern tip of the South China Sea. It is separated from the West Natuna Basin by a basement high called the Natuna Arch. The Bunguran Trough bounds the eastern side of East Natuna Basin from Sarawak Basin, offshore East Malaysia. The northern part of the East Natuna Basin has similar geological setting with the Nam Con Son Basin, offshore Vietnam.Petroleum exploration activity in this area is relatively low in comparison to it is in the West Natuna Basin. In 1973, Agip discovered Natuna D-Alpha gas field in the East Natuna Basin. The field contains more than 200TCF of gas, but unfortunately, the gas has 71% CO2. Recently, Premier Oil successfully tested the synrift play in the north of the region by drilling Kuda Laut-1 (2014) and then followed it up in the same year with drilling Singa Laut-1. The results also proved equivalent synrift play in the north within Vietnamese waters. A younger clastic play in the south of the East Natuna Basin was already proven earlier in 2012, by Black Platinum Energy (BPE) as a result of the Dara-3 and 4 drilling campaign.This article presents a summary of seismic sections published in the area with interesting geological features such as carbonate build-ups, synrift fault blocks and relatively simple anticlinal features at younger intervals. Other potential hydrocarbon accumulations are also discussed here.